LATVIAN HIGHER EDUCATION INSTITUTION STUDENT FOREIGN LANGUAGE LEARNING STRATEGIES - Jakovļeva, Monta; Rudzinska, Ieva; Jakovļeva, Gita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The study focused on the frequencies of Latvian higher education institution student self-reported foreign language learning strategies. From the 86 participants 44 were males and 42 – females; sport science was studied by 48 respondents, and health care by 38; 44.20% were freshmen and 55.80% - sophomores; 76.70% were full-time and 23.30% – part-time students. The study employed the Strategy Inventory for Foreign Language Learning (SILL), consisting of 50 statements divided into 6 categories: memory, cognitive, compensation, metacognitive, social and affective. One statement from the memory strategies was removed, as it was considered non-relevant for the students. Likert scale of three choices - never, sometimes and often – was used. SPSS Version 26 was used for the data analysis. Results: 1) the investigated students tended to use cognitive (mean =2.12; st.dev.=0.29; min,=1,43; max.=3) and compensation (mean =2.11; st.dev.=0.36; min.=1,33; max.=2.83) strategies more often; 2) the students tended to use affective (mean =1.78; st.dev.=0.39; min.=1.00; max.=2.67) strategies less often; Wilcoxon Signed Ranks Test showed that compensation strategies are used more often than memory strategies (Z=5.08; Sig. =0.00) and metacognitive strategies were used more often than affective strategies (Z=5.00; Sig. =0.00).